LESSON STUDY SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM PENILAIAN HASIL BELAJAR PADA MASA PANDEMI COVID 19 DI SDN TANJUNG MAS SEMARANG - Lestari, Siti (Persatuan Guru Republik Indonesia Kota Semarang, 2021)
COVID-19 is so big for education to break the chain of transmission of the COVID-19 pandemic, learning that is usually done at school is now learning at home using various applications. However, during the learning process carried out from home, the teachers of Tanjung Mas Elementary School, North Semarang Sub-district, experienced difficulties in assessing and reporting the development of students. only done by teachers based on assignments that students do and not systematically, teachers are not able to carry out assessments by conducting KKM documents, conducting tests, attitude assessments, assessments, skills assessments, daily analysis, remedial, enrichment, analysis of assessment items and question banks, from 15 There are only 6 teachers who conduct student assessments according to the rules. Therefore, teachers need lesson study activities. This study aims to answer the problems of 1) looking for lessons as an effort to increase the ability of teachers in assessing learning outcomes during the covid 19 pandemic at SDN Tanjung Mas, North Semarang District, for the 2020/2021 academic year? 2) the implementation of lesson study can improve the ability of teachers in assessing learning outcomes during the covid 19 pandemic at Tanjung Mas Elementary School, North Semarang District, for the 2020/2021 academic year?. The problem is discussed through school action research which is carried out through 2 cycles with each cycle the stages are planning, action, observation, and reflection. The results showed: 1) Lesson Study implementation as an effort to improve teacher ability in assessing learning outcomes during the covid 19 pandemic was carried out by providing opportunities for group teachers with one teacher being a model teacher and another member being an observer, any problems that occurred working in the workplace. group and discussed with other groups, the position of the researcher is to provide guidance and motivation for teacher group work to occur. 2) The implementation of lesson study can improve the ability of teachers in terms of learning outcomes during the COVID-19 pandemic at Tanjung Mas Elementary School, North Semarang District, for the 2020/2021 academic year, this can be seen from the increase in the results of teacher professionalism in classroom administration management per cycle in cycle I. teachers or 47%, and in the second cycle there were 13 teachers or 87%. These results indicate that these results are in line with expectations. It also occurred in teacher activities in the improvement of mini workshops where in the first cycle there were 10 teachers or 67%. And up in the second cycle there were 13 teachers or 87%. The increase in the implementation of mini workshops is one way for school principals to improve the ability of teachers to develop learning tools.